Optimization of extraction and physicochemical properties of gelatin from pangasius catfish (Pangasius sutchi) skin - Mahmoodani, Fatemeh; Ardekani, Venus Sanaei; See, Siau Fern; Salma Mohamad Yusop; Abdul Salam Babji (Universiti Kebangsaan Malaysia, 2014)
In order to optimize the extraction of gelatin from pangasius catfish skin, a response surface method (RSM) involving a Central Composite Design (CCD) was applied. Four variables, namely NaOH concentration (0-0.3 N), acetic acid concentration (0.025-0.125 N), extraction time (2-4 h) and extraction temperature (40-80°C) were selected as independent variables for the optimization using RSM. The dependent variable was calculated by hydroxyproline recovery. The optimum conditions for extraction were produced by a pre-treatment of 0.2 N NaOH and 0.1 N acetic acid along with hot water extraction at 63.7°C for 2.41 h. The results showed that the predicted response by RSM (68.53%) closely matched the experimental response of 68.16%. The results indicated that the extracted gelatin possessed high gel strength (438 g) and high content of imino acid (proline and hydroxyproline) (18.01%) with a viscosity of 4.67 mPa s. The results showed that RSM was a great optimizing tool for extraction of gelatin from pangasius catfish skin. The gelatin was also proven to have significantly (p<0.05) higher quality of physicochemical properties than those from bovine skin gelatin.